A Systematic Review on the Effects of Epichloë Fungal Endophytes on Drought Tolerance in Cool-Season Grasses - Decunta, Facundo A.; Pérez, Luis I.; Malinowski, Dariusz P.; Molina-Montenegro, Marco A.; Gundel, Pedro E. (Frontiers in Plant Science, 2021)
Symptomless fungal endophytes in the genus Epichloë are repeatedly mentioned to increase tolerance of cool-season grasses to a wide range of environmental stress factors, mainly drought. However, the generality of this idea is challenged because (i) most studies have been conducted on two economically important forage grasses [tall fescue (Festuca arundinacea (Schreb.) Dumort) and perennial ryegrass (Lolium perenne L.)], (ii) endophyte-mediated mechanisms and effects on plant responses to drought have shown to be highly variable across species, and that (iii) symbiosis incidence in plant populations occurring in extremely arid environments is usually low. We question this idea by reviewing the existing information about Epichloë fungal endophyte effects on drought tolerance in cool-season grasses. We combined standard review, vote counting, and calculation of effect sizes to synthesize the literature, identify information gaps, and guide future research. The total number of studies we higher for domesticated than for wild species; a ratio that was balanced when papers with data quality for effect size calculus were considered. After the drought, endophyte-infected plants accumulated more aboveground and belowground biomass than non-infected counterparts, while no effect on tillering was observed. However, these effects remained significant for wild (even for tillering) but not for domesticated species. Interestingly, despite the continuous effect in determinating physiological mechanisms behind the endophyte effects, no studies evaluated plant fecundity as a measure of ecological fitness nor vital rates (such as survival) as to escalate individual-level variables to population. Together with the high variability in results, our work shows that generalizing a positive effect of fungal endophytes in plant tolerance to drought may be misleading. Future studies combining field surveys with manipulative experiments would allow us to unravel the role of fungal endophytes in plant adaptation by considering the evolutionary history of species and populations to a given ecological context.